When cats dream - Pilkey, Dav, 1966- (New York : Orchard Books, 1992)
When cats dream, they can do anything they want, from combing their hair with the moon to swinging from vines in the jungle.
"A Richard Jackson book"--Half t.p.
4/7; PreS/2 (cover)
Keywords: Cats -- Fiction; Dreams -- Fiction